Atomic force microscopy force‐distance curves with small amplitude ultrasonic modulation. Issue 4 (27th April 2015) - Ma, Chengfu; Chen, Yuhang; Wang, Tian; Chu, Jiaru
Summary Force‐distance curves were acquired on a highly oriented pyrolytic graphite (HOPG) specimen and a gold film specimen under ultrasonic modulation in atomic force microscopy (AFM). Measurements demonstrated that small amplitude ultrasonic oscillation of either the cantilever or the sample has significant impacts on the characteristics of force‐distance curves. With the increase of excitation amplitude, the apparent pull‐off force decreased gradually and the hysteresis between the approach and retraction curves reduced significantly. Furthermore, the decrease of the pull‐off force was determined to be also relevant to the excitation frequency. With the assistance of contact resonance spectra, the pull‐off force was verified to have a near‐linear relationship with the cantilever contact oscillation amplitude. Theoretical analysis and subsequent numerical simulations well interpreted the experimental results. The emergence of large oscillating contact forces under ultrasonic modulation altered the force‐distance curves, and such a mechanism was ascertained by further ultrasonic AFM imaging. SCANNING 37:284–293, 2015. © 2015 Wiley Periodicals, Inc.